Copper‐Based Metal–Organic Porous Materials for CO2 Electrocatalytic Reduction to Alcohols. Issue 6 (25th August 2016) - Albo, Jonathan; Vallejo, Daniel; Beobide, Garikoitz; Castillo, Oscar; Castaño, Pedro; Irabien, Angel
Abstract: The electrocatalytic reduction of CO2 has been investigated using four Cu‐based metal–organic porous materials supported on gas diffusion electrodes, namely, (1) HKUST‐1 metal–organic framework (MOF), [Cu3 (μ6 ‐C9 H3 O6 )2 ] n ; (2) CuAdeAce MOF, [Cu3 (μ3 ‐C5 H4 N5 )2 ] n ; (3) CuDTA mesoporous metal–organic aerogel (MOA), [Cu(μ‐C2 H2 N2 S2 )] n ; and (4) CuZnDTA MOA, [Cu0.6 Zn0.4 (μ‐C2 H2 N2 S2 )] n . The electrodes show relatively high surface areas, accessibilities, and exposure of the Cu catalytic centers as well as favorable electrocatalytic CO2 reduction performance, that is, they have a high efficiency for the production of methanol and ethanol in the liquid phase. The maximum cumulative Faradaic efficiencies for CO2 conversion at HKUST‐1‐, CuAdeAce‐, CuDTA‐, and CuZnDTA‐based electrodes are 15.9, 1.2, 6, and 9.9 %, respectively, at a current density of 10 mA cm −2, an electrolyte‐flow/area ratio of 3 mL min cm −2, and a gas‐flow/area ratio of 20 mL min cm −2 . We can correlate these observations with the structural features of the electrodes. Furthermore, HKUST‐1‐ and CuZnDTA‐based electrodes show stable electrocatalytic performance for 17 and 12 h, respectively. Abstract : Closing the loop : Metal–organic porous materials are effective electrocatalysts for the continuous electrochemical conversion of CO2 to alcohols, a process that could promote the transition to a low‐carbon economy. The modularity of these systems yields many opportunities for further performance improvements and opens new directions in electrocatalysis.